2006
DOI: 10.1016/j.jmmm.2006.02.273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic core geometry on false detection in residual current sensor

Abstract: Under high-supply current, residual circuit breakers are subject to abnormal tripping, caused by false residual currents. Geometric or magnetic anomalies in the circuit breaker ring core seem to be responsible for these abnormal currents. This paper studies a few anomalies (spiral shape effect, conductor eccentricity, lamination effect) and calculates different contributions using the finite element simulations. The results show that the ring core, made of thin wound magnetic tape, is particularly sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…But the analytical relationship of f(dj) is hard to obtain. [5] IV. RCT SIMULA nON AND ANALYSIS As above mentioned, eccentricity /) of conductors in the primary winding and spiral angle <p of the magnetic core have great effect on the transformer.…”
Section: V5-27mentioning
confidence: 99%
“…But the analytical relationship of f(dj) is hard to obtain. [5] IV. RCT SIMULA nON AND ANALYSIS As above mentioned, eccentricity /) of conductors in the primary winding and spiral angle <p of the magnetic core have great effect on the transformer.…”
Section: V5-27mentioning
confidence: 99%
“…They may cause concentration of the flux to the first layer, which can be saturated. These errors are not only of concern in the case of precise sensors, such as current comparators -they may cause abnormal tripping of ordinary current breakers [Colin 2006]. Wide bandwidth: a large frequency range from DC to several MHz is required for applications in switching power converters.…”
Section: Current Sensor Parametersmentioning
confidence: 99%
“…They may cause concentration of the flux to the first layer, which can be saturated. These errors are not only of concern in the case of precise sensors such as current comparators, but they may also cause abnormal tripping of ordinary current breakers (Colin et al 2006).…”
Section: Current Sensor Parametersmentioning
confidence: 99%
“…The ribbon is wound in a spiral manner that has an influence on FRCs. Paper (Colin et al , 2006) shows that the effect of the spiral shape can be separated of others FRC sources. Thus, in this paper, the real spiral shape was replaced by concentric layers.…”
Section: 2d Simulation Of a Multilayer Magnetic Corementioning
confidence: 99%
“…It is strongly suspected that the geometry of the core has a notable impact on the FRC. It has been previously shown that the position of the ribbon ends had an influence on FRC (Colin et al , 2006). This paper concentrates on the multilayer core modelling and its effects.…”
Section: Introductionmentioning
confidence: 99%